1-[(E)-(3-Hydroxy-4-methoxybenzylidene)amino]- 3-methylthiourea - Arafath, Md. Azharul; Adam, Farook; Razali, Mohd. R. (International Union of Crystallography, 2016)
In the title thiosemicarbazone Schiff base compound, C10H13N3O2S, the dihedral angle between the benzene ring and methyl carbothioamide side arm was found to be 17.4 (4). The presence of two intramolecular hydrogen bonds is noted, namely hydroxy-O—H O(methoxy) and amine-N—H N(imine). In the crystal, pairwise amine-N—H S hydrogen bonds give rise to centrosymmetric { HNCS}2 synthons, which lead to dimeric aggregates.